Length-weight relationships and relative condition factor of fish species dwelling in the inland saline river, Luni, India, with a note on the associated risks and encounters obstructing the fish diversity and ecosystem services: Length-weight relationships and relative condition factor of fishes of Luni River, India - PATHAK, AJEY KUMAR; Ganesan Kantharajan; DAYAL, RAJESH; KUMAR, RAVI; V. P. SAINI; MOHINDRA, VINDHYA; LAL, KULDEEP K. (Indian Journal of Fisheries, 2022)
Luni is an ephemeral and inland saline river flowing through the Thar Desert of India. The present study focusses on the length-weight relationships (LWRs) and condition factor analysis of six native and one invasive alien fish species (Oreochromis mossambicus) collected from the river Luni during the exploratory surveys conducted from October, 2018 to September, 2020. LWRs of native fish species showed negative allometric growth for Aphanius dispar, Cirrhinus mrigalaand Salmostoma bacaila and positive allometric growth for Labeo rohita, Mystus gulio and Systomus sarana. Despite abundant distribution of O. mossambicus in the middle and downstream segments of the river Luni, this study revealed good wellbeing and suitability of this river to native and non-native fish species. This forms the first study that reports the LWRs and Kn value of these fish species from the river Luni, which could be useful for estimating stock characteristics and future evaluation of fish population in this dynamic and fragile ecosystem. Further, results of the present study were also compared with the available literature from nearby and associated ecosystems. The baseline information generated will be helpful in understanding the present status of the fish population and also to carryout ecological studies for their conservation and management in the future.Keywords: Invasive Alien Species, Length-weight relationship, Oreochromis mossambicus, Thar Desert